Six Minute Walk Test (6mwt) sebagai Indikator Pemulihan Fungsional Fase Rehabilitasi Jantung Pasca Sindrom Koroner Akut: Scoping Review - Subhan Ulan; Azizah Khoiriyati; Erna Rochmawati (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The Six Minute Walk Test (6MWT) is widely used as a simple and practical measurement tool to assess patients' functional abilities, but the variations in its use and implementation in various cardiac rehabilitation contexts have not been comprehensively mapped. Acute coronary syndrome (ACS) is the leading cause of cardiovascular morbidity and mortality worldwide, making the recovery of functional capacity a primary focus in cardiac rehabilitation. This study aims to map the scientific evidence regarding the use of the 6MWT as an indicator of functional capacity recovery in post-ACS patients across various cardiac rehabilitation models. This study uses a scoping review approach based on the Arksey O’Malley (2005) framework and the PRISMA-ScR (2018) guidelines. Literature search was conducted on the Scopus, PubMed, Cochrane Library, and Google Scholar databases for the period 2015–2025. Inclusion criteria included quantitative studies on adult post ACS patients using the 6MWT in cardiac rehabilitation. A total of 10 studies met the criteria and were thematically analysed using the PCC framework.  The analysis results show that the 6MWT is consistently used as the primary indicator of functional capacity recovery, with a significant increase in distance covered after cardiac rehabilitation. Three main themes were identified, namely 6MWT as the Primary Indicator of Functional Recovery, the Effectiveness of Cardiac Rehabilitation Models on 6MWT Outcomes, and the Relationship between 6MWT and Clinical and Psychosocial Outcomes. The study was dominated by China, followed by Iran, South Korea, Germany, and Indonesia. The 6MWT is a valid, practical, and versatile measurement tool for assessing post ACS patient recovery in various cardiac rehabilitation contexts. The integration of the 6MWT in clinical practice has the potential to enhance rehabilitation monitoring and support the prevention of long-term complications. Keywords: Functional Capacity, Cardiac Rehabilitation, Acute Coronary Syndrome, Six-Minute Walk Test, Scoping Review.  ABSTRAK Six Minute Walk Test (6MWT) banyak digunakan sebagai alat ukur sederhana dan praktis untuk menilai kemampuan fungsional pasien, namun variasi penggunaan dan implementasinya dalam berbagai konteks rehabilitasi jantung belum terpetakan secara komprehensif. Sindrom koroner akut (SKA) merupakan penyebab utama morbiditas dan mortalitas kardiovaskular di dunia, sehingga pemulihan kapasitas fungsional menjadi fokus utama dalam rehabilitasi jantung. Penelitian ini bertujuan untuk memetakan bukti ilmiah mengenai penggunaan 6MWT sebagai indikator pemulihan kapasitas fungsional pada pasien pasca SKA dalam berbagai model rehabilitasi jantung. Penelitian ini menggunakan pendekatan scoping review berdasarkan kerangka Arksey O’Malley (2005) dan panduan PRISMA-ScR (2018). Penelusuran literatur dilakukan pada database Scopus, PubMed, Cochrane Library, dan Google Scholar untuk periode 2015–2025. Kriteria inklusi mencakup studi kuantitatif pada pasien dewasa pasca SKA yang menggunakan 6MWT dalam rehabilitasi jantung. Sebanyak 10 studi memenuhi kriteria dan dianalisis secara tematik menggunakan kerangka PCC. Hasil analisis menunjukkan bahwa 6MWT secara konsisten digunakan sebagai indikator utama pemulihan kapasitas fungsional, dengan peningkatan jarak tempuh yang signifikan setelah rehabilitasi jantung. Tiga tema utama teridentifikasi, yaitu 6MWT sebagai Indikator Utama Pemulihan Fungsional, Efektivitas Model Rehabilitasi Jantung terhadap Hasil 6MWT, Hubungan 6MWT dengan Outcome Klinis dan Psikososial. Studi didominasi oleh negara Tiongkok, diikuti Iran, Korea Selatan, Jerman, dan Indonesia.  6MWT merupakan alat ukur yang valid, praktis, dan serbaguna dalam menilai pemulihan pasien pasca SKA di berbagai konteks rehabilitasi jantung. Integrasi 6MWT dalam praktik klinis berpotensi meningkatkan pemantauan rehabilitasi dan mendukung pencegahan komplikasi jangka panjang. Kata Kunci: Kapasitas Fungsional, Rehabilitasi Jantung, Sindrom Koroner Akut, Six-Minute Walk Test, Scoping Review.